Cultura de segurança do paciente em hospital universitário durante a pandemia da COVID-19 - Prieto, Marcela Moreira Nascimento (Universidade Federal de São Carlos, 2021)
The evaluation of the safety culture allows to eobtain a clear view of the aspects related to patient safety that need adjustments and require more attention, enabling the institution to improve its work processes. The current pandemic of COVID-19 has generated several changes in health organizations that directly impact the performance of professionals and patient safety. In this context, this research sought to answer the following question: What is the culture of patient safety in a university hospital and its interface with COVID-19 from the perspective of health professionals? This research aimed to evaluate the patient safety culture in a university hospital during the COVID-19 pandemic. This is a descriptive, cross-sectional, Survey type study with a quantitative approach, by applying the Hospital Survey on Patient Safety Culture questionnaire to professionals who work directly and indirectly in patient care. 336 health professionals working at the hospital were invited to participate in the research. The questionnaire was sent by email to the participants and the data collection took place from December 1, 2020 to January 15, 2021. The data were submitted to descriptive analysis guided by the User’s Guide of the Agency for Healthcare Research and Quality. The rate of response to the questionnaire was 6.54% in the hospital as a whole and 23.07% among nursing technicians in Pediatrics. No dimension was considered strengthened. Two dimensions were considered neutral in the general analysis and five dimensions were considered neutral in the analysis of Pediatrics. The most critical dimensions, which presented the worst index of positive responses, were: “Nonpunitive response to error”, “Frequency of event reporting”, “Staffing”, “Teamwork across hospital units”, “Feedback and communication about error", "Supervisor/manager expectations and actions promoting patient safety"," Overall perceptions of safety". The survey results are in line with other surveys that did not have strengthened dimensions and whose dimension “Nonpunitive response to error” is considered critical. It was not possible to correlate the results with the COVID-19 pandemic due to the absence of a previous study that evaluated the patient safety culture at the institution.
Culture of patient safety in a university hospital during a COVID-19 pandemic
Keywords: Segurança do paciente; Cultura organizacional; COVID-19; Patient safety; Organizational culture; Quality of Health Care; CIENCIAS DA SAUDE::ENFERMAGEM